Self-regulated learning strategies adopted by successful Chinese nursing students in the process of learning Nursing English. - Lina Wang; Xuesong Andy Gao; Fan Zhang; Fang Sun; Guangsheng Wan (PLoS ONE)
As the number of foreign patients and the frequency of international academic exchanges increase, English proficiency has become increasingly essential for Chinese nurses in the treatment and nursing processes, clinical academic exchanges, and ongoing education. However, the overall English proficiency of Chinese nurses is generally inadequate, greatly depending on the English that they acquire during their nursing education. This study aims to explore the challenges encountered by Chinese EFL (English as a Foreign Language) nursing students in the process of learning Nursing English, along with the effective self-regulated learning strategies they adopt to overcome these challenges. Data were collected from nine Chinese EFL nursing students through their reflective journals and thematic analysis was applied. Data analysis revealed the variety of challenges EFL nursing students encountered, including language-related challenges, which are linguistic difficulties that relate to Nursing English learning itself, such as Nursing English vocabulary and terminology, English-to-English translation, limited listening comprehension, and the gap between textbook knowledge and its practical application; learner-related challenges, which are difficulties that affect students' emotional, affective, and mental state, primarily caused by uncertainty about the significance of Nursing English, the unexpected difficulty of Nursing English, and failing quizzes; and context-related challenges, which are difficulties relate to social, cultural, and educational context, such as insufficient learning resources, a lack of language environment, and peer pressure. To surmount these challenges, the participants adopted diverse self-regulated learning strategies, including setting goals, previewing in advance and reviewing in time, utilizing word roots, prefixes, and suffixes to facilitate vocabulary learning, repeating, practicing with sounds and writing systems, translating, highlighting and using imagery to overcome language-related challenges; believing in the usefulness and significance of Nursing English, keeping a growth mindset, enjoying Nursing English learning and teacher support and maintaining grit in learning Nursing English to overcome learner-related challenges; and integrating resources, creating supportive language environments and seeking assistance from teachers and cooperating with peers to overcome context-related challenges. Based on these findings, implications are drawn for Nursing English teachers, material designers, curriculum developers, and program designers. We suggest incorporating explicit strategy instruction into regular Nursing English education to enhance nursing students' self-regulated learning.